THE EFFECT OF PROFITABILITY AND ENVIRONMENTAL PERFORMANCE ON THE DISCLOSURE OF CARBON EMISSIONS WITH MANAGERIAL OWNERSHIP AS A MODERATING VARIABLE - Andi Nurlailiah Hamdiyani (Jurnal Magister Akuntansi Trisakti, 2023)
This study aims to examine the effect of profitability and environmental performance on the disclosure of carbon emissions with managerial ownership as moderating. The population in this study are manufacturing companies listed on the IDX and listed on the PROPER rating of the Ministry of Environment for the period 2016 – 2019. The sample selection used the purposive sampling method, obtained a sample of 20 companies. The data analysis technique used is hierarchical moderating regression analysis. The results show that environmental performance and profitability have a positive effect on disclosure of carbon emissions and managerial ownership is able to moderate profitability and environmental performance on disclosure of carbon emissions.